Support to Micro, Small and Medium Enterprises in Organic Clusters Project - Lotfy, Liana (2018)
As part of IFPRI Egypt Seminar in partnership with the Egyptian Center for Economic Studies: "Unleashing Untapped Potential of Industrial Clusters in Egypt"